The state of tear production in patients with cicatricial changes of the conjunctiva and cornea after severe eye burns and investigation of the possibilities of treatment of dry eye syndrome in these patients (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Many patients with cicatricial changes in the conjunctiva and cornea after severe eye burns develop dry eye syndrome (DES). Objective. To examine the degree of impairment of tear production in patients with scar consequences of severe eye burns before and after surgical treatment and to study their effectiveness in DES treatment in these patients. Material and methods. The degree of tear production was evaluated by Schirmer’s test 1 and 2. The study was performed in 95 eyes of 55 patients, including 76 eyes of 42 patients with DES and 19 eyes of 13 patients without DES. Results. It is established that the degree of DES depends on the degree of cicatricial changes of the conjunctiva (the size of symblepharone) and on the area of the transplanted lip mucosa after the removal of the latter. Conducted medication reduces to some extent the degree of DES and increased acuity of vision in these patients. Conclusion. Patients with cicatricial changes of the conjunctiva and cornea after severe eye burns often develop DES, the extent of which depends on the area of the transplanted oral mucosa after its elimination. To moisten the ocular surface such patients need constant instillation of the tear substituting fluids and gels, which should be selected individually.
Keywords: Severe eye burns; cicatricial changes; tear production; syndrome of the dry eye